2014
DOI: 10.1039/c3em00676j
|View full text |Cite
|
Sign up to set email alerts
|

Early diagenetic processes generate iron and manganese oxide layers in the sediments of Lake Baikal, Siberia

Abstract: Distinct layers of iron(III) and manganese(IV) (Fe/Mn) oxides are found buried within the reducing part of the sediments in Lake Baikal and cause considerable complexity and steep vertical gradients with respect to the redox sequence. For the on-site investigation of the responsible biogeochemical processes, we applied filter tube samplers for the extraction of sediment porewater combined with a portable capillary electrophoresis instrument for the analyses of inorganic cations and anions. On the basis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 77 publications
1
49
0
Order By: Relevance
“…Whereas the redistribution of Fe and Mn in marine sediments during early diagenesis has been extensively recorded and modeled for many years (Robbins and Callender 1975;Froelich et al 1979;Aller 1980;Kasten et al 1998), detailed studies of Fe-and Mn-rich layers in freshwater sediments are still scarce (Och et al 2012;Torres et al 2014;Granina et al 2004;Zakharova et al 2010). Particularly rare are investigations that go beyond simple geochemistry and include geomicrobiological aspects of the formation of metal-rich layers.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Whereas the redistribution of Fe and Mn in marine sediments during early diagenesis has been extensively recorded and modeled for many years (Robbins and Callender 1975;Froelich et al 1979;Aller 1980;Kasten et al 1998), detailed studies of Fe-and Mn-rich layers in freshwater sediments are still scarce (Och et al 2012;Torres et al 2014;Granina et al 2004;Zakharova et al 2010). Particularly rare are investigations that go beyond simple geochemistry and include geomicrobiological aspects of the formation of metal-rich layers.…”
Section: Introductionmentioning
confidence: 98%
“…Taking into consideration possible secondary diagenetic pathways, Och et al (2012) hypothesized that Fe and Mn layers could have resulted from recycling of Fe and Mn oxides, which consist of reductive dissolution of Fe and Mn oxides below the O 2 penetration depth, followed by Fe and Mn oxides precipitation and accumulation. Indeed, in a recent study in Lake Baikal, Torres et al (2014) found that Fe and Mn layers can be formed by dissolution of particulate Fe and Mn coupled to the anaerobic oxidation of methane. Dissolved Fe(II) diffuses upward to reduce particulate Mn(IV) and thus forming a sharp mineral boundary.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results show that the AAA directly coupled the reduction of these environmentally relevant, particulate oxidized metal species to methane oxidation and could play an as-yet largely overlooked role in decreasing methane emissions from anoxic environments to the atmosphere. Given the 8:1 stoichiometry of Fe 3+ reduced to methane oxidized [3], their contribution to iron cycling, thereby impacting also the geochemistry of phosphorus and sulfur, may be even more important than their impact on the carbon cycle (11,16,18,20). The enrichment of at least one of the microbial players not only now enables a targeted investigation of iron-dependent methane oxidation in physiological and molecular detail, but may also shed light on the long-standing discussion about Fe 2+ -producing processes on early Earth, when AAA-related organisms may have thrived under the methane-rich atmosphere in the ferruginous Archean oceans (12,18,30).…”
Section: Significancementioning
confidence: 99%
“…By geochemical profiling or isotope tracer studies, the coupling of methane oxidation to metal reduction has been demonstrated or suggested in lake sediments (9)(10)(11), lake water (12), a contaminated aquifer (13), a mud volcano (14), and marine sediments (15)(16)(17)(18). The possible role of a cryptic sulfur cycle supplying sulfate via Fe 3+ -mediated reoxidation of sulfides (19,20) could often not be excluded in these studies, and none of them identified the microorganisms responsible for the process nor succeeded in obtaining an enrichment…”
mentioning
confidence: 99%